Whole-body kinematics during a simulated sprint in flat-water kayakers - Bertozzi, F.; Porcelli, S.; Marzorati, M.; Pilotto, A. M.; Galli, M.; Sforza, C.; Zago, M. (European Journal of Sport Science, 2022)
Success in sprint kayaking depends on the propulsive power generated by trunk, pelvis, shoulder and lower limb movements. However, no studies have examined whole-body kinematics over a simulated distance. We aimed to study the changes in movement patterns of kayakers performing a 500-m kayak sprint. Eleven young K1 sprint kayakers (three females; age: 16.5 ± 1.9 years, height: 174.1 ± 7.1 cm and weight: 66.1 ± 6.2 kg) performed an incremental test on a kayak ergometer to assess their Peak Oxygen Uptake (VO2peak). They then performed a 500-m sprint trial on the same ergometer, and the positions of 40 reflective markers were recorded to assess whole-body kinematics. Joint angles over time were computed for the trunk and right shoulder, hip, knee, and ankle. Changes of joint kinematics during the test were assessed with Statistical Parametric Mapping, calculating at each time node the linear regression between joint angles waveforms and the time of the rowing cycle, p < .05. Cardiometabolic responses confirmed that the participants achieved a maximal effort (VO2 and HR reached 99 ± 11% and 94 ± 6% of peak values, respectively). Paddle velocity negatively correlated with sprint time. The shoulder (elevation, rotation and flexion), trunk (lateral flexion and rotation) and hip (abduction) angles significantly changed over time in different phases of the stroke cycle during the simulated sprint. No significant differences over time were found for knee and ankle flexion. A high-intensity sprint may affect the shoulder, trunk and hip kinematics of kayak paddling. The kinematic analysis of kayakers` paddling during simulated metabolic-demanding tasks can provide useful insights to coaches and athletes.